Bacterial cellulose composite powder and its manufacturing method
By culturing bacterial cellulose with specific polymeric substances and combining them before drying, the bacterial cellulose complex powder achieves uniform dispersion and high viscosity in salt-containing liquids, addressing aggregation and dispersibility issues in existing powders.
Patent Information
- Application Number
- JP2024026193
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-26
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-02-12
AI Technical Summary
Existing bacterial cellulose powders face challenges in uniform dispersion in liquids containing salts without mechanical stirring, and they often aggregate during drying due to hydrogen bonding, leading to reduced dispersibility and solubility.
A bacterial cellulose complex powder is produced by culturing bacterial cellulose in the presence of a first polymeric substance, such as hydroxypropylcellulose or hydroxyethylcellulose, and then adding a second polymeric substance, including hydroxypropylcellulose, hydroxyethylcellulose, xanthan gum, sodium alginate, or polyglycolic acid, before drying.
The resulting bacterial cellulose complex powder can be uniformly dispersed in liquids containing salts without mechanical stirring, developing viscosity effectively, and maintaining high dispersibility even in salt solutions.
Smart Images

Figure 0007663210000007 
Figure 0007663210000008 
Figure 0007663210000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a bacterial cellulose composite powder and a method for producing the same. [Background technology]
[0002] Bacterial cellulose (NFBC) is generally produced in the form of a paste dispersed in water. Therefore, when bacterial cellulose is used in food, there is concern about the problem of contamination by various bacteria. Furthermore, since paste-like bacterial cellulose contains a large amount of water, it is costly to transport. Therefore, powderization of bacterial cellulose is being considered so that it can be used at low cost.
[0003] Powdered bacterial cellulose is required to return to the same dispersion state as before powderization when dispersed in water. In addition, in order to be compatible with a variety of foods and solutions, powdered bacterial cellulose is required to be easily dispersed and dissolved in solutions containing salts such as table salt, and to return to the dispersion state before powderization.
[0004] However, when paste-like bacterial cellulose is dried, the bacterial cellulose molecules are strongly bonded to each other through hydrogen bonds, causing the cellulose molecules to aggregate. Even if the aggregated bacterial cellulose is suspended again in water, the cellulose molecules cannot spread out, and viscosity does not appear. To obtain bacterial cellulose powder that can be redispersed in water, it is necessary to prevent the aggregation of cellulose molecules in the drying process. As a method for suppressing aggregation during drying, a method of combining bacterial cellulose with a polymeric substance has been reported (e.g., Patent Documents 1 and 2).
[0005] Meanwhile, bacterial cellulose produced by stirring culture in a medium containing carboxymethylcellulose (CMC) has been reported (for example, Patent Document 3). This bacterial cellulose is a thin, long, uniform fiber, and CMC is bound to the surface of cellulose microfibrils by electrostatic repulsion or the like. Furthermore, dried bacterial cellulose containing CMC, hydroxypropyl cellulose (HPC), and hydroxyethyl cellulose (HEC) has been described (e.g., Patent Document 4). It has also been described that a dried solid of cellulose nanofiber containing 5 to 300% by weight of a water-soluble polymer exhibits properties equivalent to those before drying when dissolved in water (e.g., Reference 5). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-121787 [Patent Document 2] Japanese Patent Application Publication No. 11-178516 [Patent Document 3] Patent No. 5752332 [Patent Document 4] International Publication No. 2018 / 038055 [Patent Document 5] JP 2017-8176 A Summary of the Invention [Problem to be solved by the invention]
[0007] Patent Document 1 describes a composite obtained by combining cellulose derived from microorganisms with an anionic substance. The interaction between the cellulose molecules and the anionic substance inhibits the association of the cellulose molecules with each other, and aggregation can be suppressed when the composite is dried. However, the dried product of the composite described in Patent Document 1 requires a dispersion treatment by a mechanical method to sufficiently loosen the fibers before use.
[0008] In Patent Document 1, the cellulose derived from microorganisms is not nanosized, so the individual particles are large. Since large particles cannot be broken unless a strong impact is applied, for example, if the dispersion treatment using a mixer or stirrer is insufficient, the effect may not be obtained.
[0009] Patent Document 2 discloses a dispersion stabilizing composition for food, which contains an alkali salt of bacterial cellulose and carboxymethyl cellulose (CMC). This dispersion stabilizing composition can maintain the uniformity of food ingredients without causing food to aggregate even after heat sterilization. However, for the same reason as Patent Document 1, when added to food, it is recommended to use a concentration of about 100 to 200 kg / cm. 2 It is recommended to homogenize at a pressure of 1000 MPa.
[0010] The bacterial cellulose described in Patent Documents 3 and 4 is a thin, long, uniform fiber with CMC, HPC, and HEC bound to the surface, and has high dispersibility such that it is dispersed almost uniformly in both organic and aqueous liquids. However, there is no description of the dispersibility or solubility of this bacterial cellulose in a salt solution when it is dried. Reference 5 does not describe a dry solid that can be sufficiently dispersed in a liquid containing salts.
[0011] Therefore, an object of the present invention is to provide a bacterial cellulose composite powder that can be uniformly dispersed and exhibit viscosity even in a liquid containing salts without mechanical stirring, and a method for producing the same. [Means for solving the problem]
[0012] As a result of intensive research to solve the above problems, the inventors have discovered that by drying a mixed solution in which a predetermined second polymeric substance is added to a solution of bacterial cellulose cultured in a medium containing a predetermined first polymeric substance, a bacterial cellulose composite powder can be obtained that can be uniformly dispersed and exhibit viscosity even in liquids containing salts without mechanical stirring, and has thus arrived at the present invention.
[0013] In other words, the bacterial cellulose composite powder of the present invention is produced by culturing bacterial cellulose in the presence of a first polymeric substance consisting of at least one of hydroxypropyl cellulose and hydroxyethyl cellulose, and after culturing, adding a second polymeric substance consisting of at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, xanthan gum, sodium alginate, and polyglycolic acid, and drying the resulting mixture.
[0014] Furthermore, the method for producing bacterial cellulose composite powder according to the present invention comprises culturing bacterial cellulose in the presence of a first polymeric substance consisting of at least one of hydroxypropyl cellulose and hydroxyethyl cellulose, and, after culturing, adding a second polymeric substance consisting of at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, xanthan gum, sodium alginate, and polyglycolic acid, and drying. Effect of the Invention
[0015] According to the present invention, it is possible to provide a bacterial cellulose composite powder that can be uniformly dispersed and exhibit viscosity even in a liquid containing salts without mechanical stirring, and a method for producing the same. [Brief description of the drawings]
[0016] [Figure 1] These are photographs showing the dispersion of bacterial cellulose composite powders or preparations in distilled water. Figure 1(a) is a photograph of NFBC-HPC powder, Figure 1(b) is a photograph of NFBC-CMC powder, Figure 1(c) is a photograph of Sun Artist PN, and Figure 1(d) is a photograph of Sun Artist PG. [Diagram 2] Photographs showing the dispersion of bacterial cellulose composite powder or preparation in a 0.1 wt% sodium chloride aqueous solution: Figure 2(a) is a photograph of NFBC-HPC powder, Figure 2(b) is a photograph of NFBC-CMC powder, Figure 2(c) is a photograph of Sun Artist PN, and Figure 2(d) is a photograph of Sun Artist PG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The bacterial cellulose composite powder of this embodiment contains a first polymeric substance consisting of at least one of hydroxypropyl cellulose (HPC) and hydroxyethyl cellulose (HEC), and a second polymeric substance consisting of at least one of HPC, HEC, xanthan gum, sodium alginate, and polyglycolic acid.
[0018] The bacterial cellulose composite powder of this embodiment can be produced by culturing bacterial cellulose in a medium containing a first polymeric substance, mixing a solution of the cultured bacterial cellulose with a solution of a second polymeric substance, and drying the resulting mixed solution.
[0019] In the cultured bacterial cellulose, the first polymeric substance is complexed with the bacterial cellulose. That is, the first polymeric substance is highly entangled with the bacterial cellulose. Such a first polymeric substance can be confirmed, for example, by the method described in paragraph 0084 of WO 2018 / 038055.
[0020] The first polymeric substance is composed of at least one of HPC and HEC. These are water-soluble and cold water-soluble, and react with the fibrils of bacterial cellulose. Moreover, they are approved as food additives or pharmaceutical additives, or are extracted from natural products that are used for food. Furthermore, HPC and HEC are electrically neutral since they do not have cationic or anionic groups. Since HPC and HEC are amphiphilic cellulose derivatives, bacterial cellulose obtained by culturing them in combination with each other is also amphiphilic. Considering that they can be used in food, HPC is preferable.
[0021] Such a first polymeric substance is added during bacterial cellulose production (fermentation) to culture bacterial cellulose. It is believed that the first polymeric substance binds to the surface of each cellulose microfibril that is excreted outside the bacterial cell, thereby preventing the fibrils from bundling and associating. In this way, a higher-order structure is formed while incorporating the first polymeric substance. For specific production methods, reference can be made to, for example, Japanese Patent No. 5752332 and International Publication No. WO 2018 / 038055.
[0022] The cultured bacterial cellulose has a physical property of having a light transmittance of 35% or more at a wavelength of 500 nm when contained in water at a final concentration of, for example, 0.1±0.006% (w / w). The light transmittance of water containing the cultured bacterial cellulose is an index of the dispersibility of this bacterial cellulose in water. Specifically, the higher the light transmittance, the higher the dispersibility in water.
[0023] The ratio of the first polymeric substance in the cultured bacterial cellulose is preferably 5 to 50% by weight, and more preferably about 7 to 30% by weight. For example, by adjusting the amount of the first polymeric substance, the ratio of the first polymeric substance in the cultured bacterial cellulose can be controlled within a predetermined range.
[0024] The cultured bacterial cellulose is dissolved in, for example, pure water to prepare a solution of about 0.1 to 5% by weight. By adding a solution of the second polymeric substance to the solution and drying, the cultured bacterial cellulose and the second polymeric substance are composited, i.e., highly intertwined, to obtain the desired bacterial cellulose composite powder. Before drying, it is desirable to remove impurities by filtration, centrifugation, etc.
[0025] The second polymeric substance is at least one of HPC, HEC, xanthan gum, sodium alginate, and polyglycolic acid. It is preferable that the second polymeric substance contains xanthan gum because it is highly effective in improving dispersibility. The second polymeric substance can be a polysaccharide, a derivative thereof, or a salt thereof. The second polymeric substance may be used alone or in combination of two or more kinds. The second polymeric substance may be added by dissolving it in pure water to prepare a solution of about 0.1 to 5% by weight, or may be added as a powder and dissolved.
[0026] It is believed that the second polymeric substance is dried together with the cultured bacterial cellulose and enters into the molecule. In this way, a bacterial cellulose complex containing bacterial cellulose, the first polymeric substance, and the second polymeric substance is obtained. When powdered by drying, the hydrogen bonds formed between the cellulose are weakened by the second polymeric substance, making it easier to dissolve in water, etc. The second polymeric substance in the bacterial cellulose complex can be confirmed, for example, by the amount added.
[0027] In the bacterial cellulose composite, the ratio of the cultured bacterial cellulose to the second polymeric substance (cultured bacterial cellulose:second polymeric substance) is preferably within the range of 8:2 to 2:8, and more preferably about 7:3 to 3:7. By adjusting the concentration and amount of each solution, the weight ratio of the cultured bacterial cellulose to the second polymeric substance can be controlled within a predetermined range.
[0028] In addition to the second polymeric substance, substances that are generally added as bulking agents, such as dextrin, lactose, sugars, and oligosaccharides, may be added to the cultured bacterial cellulose solution. The addition of the bulking agent increases the solid content, which leads to improved recovery (powdering). In this case, the effect of the present invention is not affected.
[0029] In the present invention, since the cultured bacterial cellulose and the second polymeric substance are mixed as solutions, it is presumed that the first polymeric substance and the second polymeric substance act on the bacterial cellulose in a complex manner. When bacterial cellulose is formed by fermentation, a higher-order structure is formed while incorporating the first polymeric substance. When it is powdered by drying, the hydrogen bonds between the cellulose are weakened by the second polymeric substance, making it easier to dissolve in water.
[0030] In addition, since HPC and HEC used as the first polymeric substance are electrically neutral, they can be easily dissolved in liquids containing salts such as sodium chloride. Thus, the effect of the bacterial cellulose composite powder of the present disclosure is achieved by the synergistic effect of the three components, bacterial cellulose, the first polymeric substance, and the second polymeric substance.
[0031] The ratio of the first polymeric substance in the cultured bacterial cellulose and the ratio of the cultured bacterial cellulose to the second polymeric substance are maintained in the bacterial cellulose composite powder after drying and pulverization. In consideration of dispersibility in liquids containing water or salts, the content of the polymeric substances (the total of the first polymeric substance and the second polymeric substance) in the bacterial cellulose composite is preferably 30 to 70%.
[0032] As described above, the bacterial cellulose composite powder of the present invention can be obtained by drying the mixed solution containing the cultured bacterial cellulose and the second polymeric substance in a thermostatic bath or the like. The temperature during drying is preferably such that the product temperature of the dried product is lower than the boiling point of the drying solvent. For example, in the case of an aqueous solution, drying is preferably performed at 100°C or lower. However, if the product temperature is lower than 100°C, the set air temperature may be 100°C or higher.
[0033] Drying at a temperature below the boiling point ensures that the viscosity is developed. Temperatures below the boiling point can avoid uneven drying caused by rapid partial drying. Moreover, there is no risk of the polymeric substance being dissolved by excessive heating, which would cause a change in the higher-order structure consisting of a complex of bacterial cellulose and polymeric substance. Vacuum drying is effective because it allows drying at a lower temperature. If a longer drying time is not a problem, freeze drying at 40°C or less can also be used.
[0034] Since the particle size of the dried product obtained by drying is not uniform, the composite product may be pulverized as necessary after drying. An impact pulverizer or the like can be used for pulverization. The size of the composite powder after pulverization is not particularly limited, but is generally about 20 μm to 500 μm. The pulverization method is also not particularly limited, and can be impact, grinding, cutting, or the like, and can be pulverized by any method.
[0035] The bacterial cellulose composite powder of the present disclosure is uniformly dispersed in liquid with weak stirring such as manual stirring and develops viscosity. Specifically, when added at a concentration of 0.1% by weight to a liquid containing salts, a viscosity of 50 mPa·s or more can be obtained at 20°C without mechanical homogenization treatment. Specifically, when the bacterial cellulose composite powder of the present disclosure is added at a concentration of 0.1% by weight to a 1.0% by weight aqueous sodium chloride solution and stirred by hand, the viscosity (η(s)) at 20°C after standing for 10 minutes is 50 mPa·s or more.
[0036] In addition, the bacterial cellulose composite powder of this embodiment has a viscosity (η(w)) of 50 mPa·s or more at 20°C after being added to distilled water at a concentration of 0.1% by weight, manually stirred, and allowed to stand for 10 minutes.
[0037] Even if the same materials as those of this embodiment are used, in the case of a composite powder manufactured by a method different from that of this embodiment, strong stirring using a homogenizer or the like is required to achieve a viscosity of about 50 mPa·s under similar conditions. The composite powder of this embodiment manufactured by a specified method can achieve a viscosity of 50 mPa·s or more with just manual stirring, and can also achieve a maximum viscosity of about 500 mPa·s.
[0038] The viscosity of the solution in which the bacterial cellulose composite powder is dissolved can be measured using a B-type viscometer at 20°C, 6 rpm, and an appropriate rotor. In this embodiment, if the measured viscosity is 50 mPa s or more, the bacterial cellulose composite powder is considered to be uniformly dispersed in the liquid. The viscosity is preferably 100 mPa s or more.
[0039] When a viscosity of 50 mPa·s or more is obtained and the relationship represented by the following formula is satisfied, the bacterial cellulose composite powder of the present invention is uniformly dispersed in a liquid containing salts. η(s)≧0.3×η(w) As described above, η(s) is the viscosity at 20° C. after adding the bacterial cellulose composite powder of this embodiment at a concentration of 0.1% by weight to a 1.0% by weight aqueous sodium chloride solution, stirring by hand, and leaving to stand for 10 minutes, and η(w) is the viscosity at 20° C. after adding the bacterial cellulose composite powder of this embodiment at a concentration of 0.1% by weight to distilled water, stirring by hand, and leaving to stand for 10 minutes. In other words, if the viscosity ratio (%) expressed by the formula ((η(s) / η(w))×100) is 30% or more, the bacterial cellulose composite powder is considered to be uniformly dispersed even in a liquid containing salts.
[0040] Since the bacterial cellulose composite powder of this embodiment is manufactured by a specified method, it can be dispersed well in liquids other than water, for example, a 1 wt% sodium chloride aqueous solution, by manual stirring to obtain a sufficient viscosity. Even if a composite powder manufactured by a method different from that of this embodiment is used using the same materials as in this embodiment, the desired viscosity cannot be obtained when it is dispersed in the same sodium chloride aqueous solution by manual stirring. In addition to being dispersible in water by manual stirring, the bacterial cellulose composite powder of this embodiment is excellently characterized in that it can be dispersed in a sodium chloride aqueous solution and the like to obtain a sufficient viscosity. EXAMPLES
[0041] Examples of the present disclosure will be described in detail below, but the present invention is not limited thereto. The materials used in this example are shown below. CMC-Na: (Wako Pure Chemical Industries, Ltd.) HEC: SE600 (manufactured by Daicel Fanchem) HPC:HPC-L (Japan Sosoda) Xanthan gum: Inagel V-10 (manufactured by Ina Food Industry Co., Ltd.) Pullulan: PI-20 (Hayashibara) Locust bean gum: Inageru L-15 (manufactured by Ina Food Industry Co., Ltd.) Tara gum: Inageru Tara gum A (manufactured by Ina Food Industry) Guar gum: Inageru GR-10 (manufactured by Ina Food Industry Co., Ltd.) Glucomannan: Inagerumannan 100 (manufactured by Ina Food Industry Co., Ltd.) Tamarind gum: Inageru V-250 (manufactured by Ina Food Industry Co., Ltd.) Psyllium seed gum: Inagel A-400 (manufactured by Ina Food Industry Co., Ltd.) Gum arabic: Inagel Gum Arabic A (manufactured by Ina Food Industry Co., Ltd.) LM Pectin: Inagel JP-20 (manufactured by Ina Food Industry Co., Ltd.) HM pectin: Inagel JP-10 (manufactured by Ina Food Industry Co., Ltd.) Soybean polysaccharides: (Sanei Gen) κ-Carrageenan: Inagel E-150 (manufactured by Ina Food Industry Co., Ltd.) I-Carrageenan: V-120 (Ina Food Industry Co., Ltd.) λ-Carrageenan: V-40 (Ina Food Industry Co., Ltd.) Sodium alginate: Inagel GS-80 (manufactured by Ina Food Industry Co., Ltd.) Polyglycolic acid (PGA): (Wako Pure Chemical Industries, Ltd.) Dextrin: Pine index #2 (Matsutani Chemical Industry)
[0042] <Cultivation of bacterial cellulose> According to the method described in Example 8 of International Patent Publication No. WO2018 / 038055, bacteria were cultured in a medium containing a carbon source and a polymeric substance for culture. HPC, HEC, and CMC were prepared as polymeric substances for culture. The culture solution after culture was centrifuged (8000 rpm, 15 minutes) to collect the precipitate. A 1 (W / V)% aqueous sodium hydroxide solution was added in an amount 5 times the volume of the precipitate, and the bacteria were dissolved by shaking at 70°C and 100 rpm for 2 hours.
[0043] The mixture was then centrifuged under the same conditions, the supernatant was removed, and the precipitate was collected to remove the bacterial components in the aqueous solution. Ultrapure water was added to the mixture, centrifuged under the same conditions, and the supernatant was removed. This procedure was repeated until the pH of the precipitate reached 7 or less under humid conditions. The cultured bacterial cellulose was purified by this procedure. The proportions of each polymeric substance at the time of cultivation in the cultured bacterial cellulose were 12% by weight (CMC), 22% by weight (HEC), and 20% by weight (HPC), respectively.
[0044] The cultured bacterial cellulose was dissolved in pure water to give an aqueous solution with a concentration of 1% by weight. The name of each aqueous solution corresponds to the polymeric substance at the time of culture, as shown in Table 1 below.
[0045] [Table 1]
[0046] <Preparation of polymer solution for composite> The polymeric substances prepared for the composite were CMC-Na, HEC, HPC, xanthan gum, pullulan, locust bean gum, tara gum, guar gum, glucomannan, tamarind gum, psyllium seed gum, gum arabic, LM pectin, HM pectin, soybean polysaccharides, κ-carrageenan, λ-carrageenan, ι-carrageenan, sodium alginate, polyglycolic acid (PGA), and dextrin. Each of the composite polymeric substances was dissolved in pure water to give an aqueous solution with a concentration of 1% by weight.
[0047] In the following, a composite polymer solution is added to an aqueous solution of cultured bacterial cellulose to obtain a mixed solution containing the cultured bacterial cellulose and the composite polymer. After drying, the mixed solution is pulverized to prepare a bacterial cellulose composite powder, and the dispersibility in water or an aqueous sodium chloride solution is evaluated.
[0048] <Test Example I-1> 100g of each composite polymer solution was added to 100g of NFBC-HPC solution and stirred. The resulting mixed solution was thinly cast in a thermostatic bath at 80°C and dried to a moisture content of about 8%. It was then pulverized using a hammer mill to prepare bacterial cellulose composite powder (NFBC-HPC powder). In the bacterial cellulose composite powder, the weight ratio of the cultured bacterial cellulose to the composite polymer was about 1:1.
[0049] For comparison, the NFBC-HPC solution alone was used without adding the composite polymer solution, and was dried and pulverized in the same manner to obtain a powder.
[0050] (Evaluation of dispersibility in water and sodium chloride solution) 0.1 g of the obtained NFBC-HPC powder was added to 100 mL of distilled water and dispersed uniformly by manual stirring using a muddler. After leaving it to stand for 10 minutes, the viscosity (20°C, 6 rpm) was measured using a B-type viscometer (BROOKFIELD (LVDV-1 PRIME)) and recorded as η(w). The viscosity was also measured in the same manner, except that the distilled water was replaced with a 1.0% sodium chloride aqueous solution, and recorded as η(s). Furthermore, the viscosity ratio (%) was calculated using the formula ((η(s) / η(w))×100).
[0051] NFBC-HPC powders containing specific composite polymers exhibited viscosity in distilled water. The composite polymers, their measured viscosities (η(w), η(s)), and calculated viscosity ratios are summarized in Table 2 below.
[0052] [Table 2]
[0053] When HPC, HEC, xanthan gum, sodium alginate or PGA was used as the composite polymer, the viscosity η(s) in sodium chloride aqueous solution was 50 mPa s or more, and the viscosity ratio was 30% or more. These bacterial cellulose composite powders could be dispersed well not only in distilled water but also in a 1.0% sodium chloride aqueous solution, demonstrating their high dispersibility.
[0054] In the case of powder of cultured bacterial cellulose alone, no viscosity was observed in 1.0% sodium chloride aqueous solution.Also, when locust bean gum, tara gum, guar gum, glucomannan, κ-carrageenan, ι-carrageenan, λ-carrageenan, or dextrin was used as the composite polymer substance, no viscosity was observed at the above-mentioned concentrations.
[0055] <Test Example I-2> 100g of each composite polymer solution was added to 100g of NFBC-HEC solution and stirred. The resulting mixed solution was thinly cast in a thermostatic bath at 80°C and dried to a moisture content of about 8%. It was then pulverized using a hammer mill to prepare bacterial cellulose composite powder (NFBC-HEC powder). In the bacterial cellulose composite powder, the weight ratio of the cultured bacterial cellulose to the composite polymer was about 1:1.
[0056] For comparison, the NFBC-HEC solution alone was used without adding the composite polymer solution, and was dried and pulverized in the same manner to obtain a powder.
[0057] (Evaluation of dispersibility in water and sodium chloride solution) 0.1 g of the obtained NFBC-HEC powder was added to 100 mL of distilled water and dispersed uniformly by manual stirring using a muddler. After leaving the mixture to stand for 10 minutes, the viscosity (20°C, 6 rpm) was measured using a B-type viscometer (BROOKFIELD (LVDV-1 PRIME)) and was taken as η(w). The viscosity was also measured in the same manner, except that the distilled water was replaced with a 1.0% aqueous sodium chloride solution, and was taken as η(s). Furthermore, the viscosity ratio (%) was calculated using the formula ((η(s) / η(w))×100).
[0058] NFBC-HEC powders containing specific composite polymers exhibited viscosity in distilled water. The composite polymers, their measured viscosities (η(w), η(s)), and calculated viscosity ratios are summarized in Table 3 below.
[0059] [Table 3]
[0060] When HPC, HEC, xanthan gum, sodium alginate or PGA was used as the composite polymer, the viscosity η(s) in sodium chloride aqueous solution was 50 mPa s or more, and the viscosity ratio was 30% or more. These bacterial cellulose composite powders could be dispersed well not only in distilled water but also in a 1.0% sodium chloride aqueous solution, demonstrating their high dispersibility.
[0061] In the case of powder of cultured bacterial cellulose alone, no viscosity was observed in 1.0% sodium chloride aqueous solution.Also, when locust bean gum, tara gum, guar gum, glucomannan, κ-carrageenan, ι-carrageenan, λ-carrageenan, or dextrin was used as the composite polymer substance, no viscosity was observed at the above-mentioned concentrations.
[0062] <Test Example I-3> 100g of each composite polymer solution was added to 100g of NFBC-CMC solution and stirred. The resulting mixed solution was thinly cast in a thermostatic bath at 80°C and dried to a moisture content of about 8%. It was then pulverized using a hammer mill to prepare bacterial cellulose composite powder (NFBC-CMC powder). In the bacterial cellulose composite powder, the weight ratio of the cultured bacterial cellulose to the composite polymer was about 1:1.
[0063] For comparison, the NFBC-CMC solution alone was used without adding the composite polymer solution, and was dried and pulverized in the same manner to obtain a powder.
[0064] (Evaluation of dispersibility in water and sodium chloride solution) 0.1 g of the obtained NFBC-HEC powder was added to 100 mL of distilled water and dispersed uniformly by manual stirring using a muddler. After leaving the mixture to stand for 10 minutes, the viscosity (20°C, 6 rpm) was measured using a B-type viscometer (BROOKFIELD (LVDV-1 PRIME)) and recorded as η(w). The viscosity was also measured in the same manner, except that the distilled water was replaced with a 1.0% sodium chloride aqueous solution, and recorded as η(s). The viscosity ratio (%) was calculated using the formula ((η(s) / η(w))×100).
[0065] NFBC-CMC powders containing specific composite polymers exhibited viscosity in distilled water. The composite polymers and the measured viscosities (η(w)) are summarized in Table 4 below.
[0066] [Table 4]
[0067] Unlike the cases of NFBC-HPC powder and NFBC-HEC powder, the viscosity of NFBC-CMC powder did not reach 50 mPa s or more in sodium chloride aqueous solution, even when HPC, HEC, xanthan gum, sodium alginate, or PGA was used as the composite polymer. NFBC-CMC powder, which is a bacterial cellulose composite powder and uses CMC as the polymer during cultivation, did not disperse well in 1.0% sodium chloride aqueous solution, indicating low dispersibility.
[0068] From the above results, it was confirmed that bacterial cellulose composite powder with the desired properties can be obtained by adding a composite polymer solution selected from HPC, HEC, xanthan gum, sodium alginate, and PGA to an aqueous solution of bacterial cellulose (NFBC-HPC solution, NFBC-HEC solution) cultured using HPC or HEC as a polymer during cultivation to composite the bacterial cellulose.
[0069] In this embodiment, the first polymeric substance is at least one selected from HPC and HEC, and the second polymeric substance is at least one selected from HPC, HEC, xanthan gum, sodium alginate, and PGA. The bacterial cellulose composite powder containing the first polymeric substance and the second polymeric substance is the bacterial cellulose composite powder of the present invention.
[0070] <Test Example II> The above-mentioned NFBC-HPC solution was used as the aqueous solution of bacterial cellulose cultured with the first polymeric substance complexed, and the above-mentioned xanthan gum solution was used as the second polymeric substance solution, and these solutions were mixed in the ratio shown in Table 5 below to prepare a mixed solution. The resulting mixed solution was thinly cast in a thermostatic bath at 80°C and dried to a moisture content of about 8%. It was then pulverized using a hammer mill to prepare a bacterial cellulose complex powder (NFBC-HPC powder).
[0071] The obtained NFBC-HPC powder (0.1 g) was added to 100 mL of distilled water and dispersed uniformly by manual stirring using a muddler to prepare a sample. After leaving the mixture to stand for 10 minutes, the viscosity (20°C, 6 rpm) was measured using a Brookfield viscometer (LVDV-1 PRIME) and recorded as η(w). The viscosity was also measured in the same manner, except that the distilled water was replaced with a 1.0% sodium chloride aqueous solution, and recorded as η(s). The viscosity ratio (%) was calculated using the formula ((η(s) / η(w))×100).
[0072] The samples whose viscosities were measured after manual mixing were further homogenized mechanically and the viscosities were measured in the same manner (20°C, 6 rpm). Specifically, the samples were processed at 100,000 rpm for 1 minute using a TK Homomixer (Mark II f model, manufactured by Tokushu Kikai Co., Ltd.). The viscosities (η(w), η(s)) were measured in the same manner as above, and the viscosity ratio ((η(s) / η(w))×100) was calculated. The viscosities (η(w), η(s)) after manual mixing and after homogenization are summarized in Table 5 below, along with the viscosity ratios.
[0073] [Table 5]
[0074] If the ratio of cultured bacterial cellulose is too high, the amount of the second polymeric substance (xanthan gum) to be complexed with the cultured bacterial cellulose may be insufficient, resulting in insufficient complexation. On the other hand, if the ratio of cultured bacterial cellulose is too low, the second polymeric substance (xanthan gum) will cover the cultured bacterial cellulose when it is dried and powdered, forming a strong coating. Since a large amount of anions are present in the coating, ionization is hindered in liquids containing salts, reducing solubility.
[0075] When the blending ratio of the cultured bacterial cellulose to the second polymeric substance (cultured bacterial cellulose:second polymeric substance) is 8:2 to 2:8, the viscosity η(s) in the sodium chloride aqueous solution is 50 mPa·s or more even after manual mixing. Therefore, at such a blending ratio, the viscosity ratio is 30% or more. From this result, the bacterial cellulose composite powder is well dispersed not only in distilled water but also in a 1.0% sodium chloride aqueous solution, and has high dispersibility.
[0076] <Test Example III> As a solution of bacterial cellulose cultured in a complex with the first polymer substance, 100 g of NFBC-HPC solution with a concentration of 1 wt% as described above was used, and as a solution of the second polymer substance, 50 g of CMC-Na solution with a concentration of 1 wt% as described above and 50 g of xanthan gum solution with a concentration of 1 wt% were added and stirred to prepare a mixed solution.
[0077] This mixed solution was thinly cast in a thermostatic bath at 80°C, dried to a moisture content of about 9%, and then pulverized in the same manner as above to obtain a bacterial cellulose composite powder. In the bacterial cellulose composite powder, the weight ratio of the cultured bacterial cellulose to the composite polymer substance was about 1:1.
[0078] Using the obtained powder, the viscosity (η(w)) in distilled water and the viscosity (η(s)) in a 1.0% sodium chloride aqueous solution were measured at 20°C and 6 rpm in the same manner as in <Test Example II>. As a result, in the case of distilled water, the viscosity after manual mixing was 450 mPa·s, and after homogenization was 470 mPa·s. In the case of a 1.0% sodium chloride aqueous solution, the viscosity after manual mixing was 150 mPa·s, and after homogenization was 180 mPa·s. The viscosity ratio was calculated to be 30% or more both after manual mixing and after homogenization.
[0079] A composite powder was prepared in the same manner, except that the NFBC-HPC solution was replaced with the same amount of powdered cellulose solution, and the viscosity of the obtained powder was measured in the same manner as above. The viscosity (η(w)) in distilled water was 10 mPa s both after manual mixing and after homogenization. The viscosity (η(s)) in a 1.0% sodium chloride aqueous solution was 0 mPa s after manual mixing and homogenization.
[0080] SunArtist® PN (manufactured by San-Ei Gen F.F.I. Co., Ltd.) was used as a powder of the complex. SunArtist® PN is a preparation containing 18.3% by weight of fermented cellulose, 6.2% by weight of CMC-Na, 12.1% by weight of xanthan gum, and 63.4% by weight of dextrin. This preparation does not contain complexed HPC or HEC.
[0081] 0.1 g of this powder was added to 100 mL of distilled water and 1.0% sodium chloride aqueous solution, and dispersed uniformly by manual stirring using a muddler. After leaving the mixture to stand for 10 minutes, the viscosity was measured (20°C, 6 rpm) using a B-type viscometer. The viscosity after manual stirring in distilled water was 110 mPa·s, and after homogenization it was 470 mPa·s. The viscosity after manual stirring in 1.0% sodium chloride aqueous solution was 0 mPa·s, and after homogenization it was 40 mPa·s.
[0082] Similar measurements were performed using Sun Artist (registered trademark) PG (manufactured by San-Ei Gen F.F.I. Co., Ltd.) as a powdered complex. Sun Artist (registered trademark) PG is a preparation containing fermented cellulose (20% by weight), CMC-Na (6.7% by weight), guar gum (6.3% by weight), and dextrin (66.6%). This preparation does not contain complexed HPC or HEC.
[0083] 0.1 g of this powder was added to 100 mL of distilled water and 1.0% sodium chloride aqueous solution, and dispersed uniformly by manual stirring using a muddler. After leaving the mixture to stand for 10 minutes, the viscosity was measured (20°C, 6 rpm) using a B-type viscometer. The viscosity after manual stirring in distilled water was 5 mPa·s, and after homogenization it was 400 mPa·s. The viscosity after manual stirring in 1.0% sodium chloride aqueous solution was 0 mPa·s, and after homogenization it was 50 mPa·s.
[0084] When the bacterial cellulose composite powder of this example was added to distilled water, the viscosity after manual stirring was the same as that after homogenization. The bacterial cellulose composite powder of this example was produced by compounding with a specific first polymeric substance and then further compounding with a specific second polymeric substance, and therefore it can be seen that it can be sufficiently dispersed even in a sodium chloride aqueous solution with weak stirring.
[0085] In contrast, when powdered cellulose that has not been complexed with a first polymeric substance and then a second polymeric substance is used, the viscosity is low even after homogenization, and it cannot be dispersed well. It has been shown that homogenization is required to disperse well for Sun Artist (registered trademark) PN and Sun Artist (registered trademark) PG, which contain bacterial cellulose that has not been complexed with a first polymeric substance selected from HPC and HEC.
[0086] <Test Example IV> A mixed solution was prepared using the same amounts of the NFBC-HPC solution, CMC-Na solution, and xanthan gum solution as in the above-mentioned <Test Example III>. This mixed solution was dried in a thermostatic bath at 60 to 140°C or by freeze-drying (40°C) to a moisture content of 8.0%, and then pulverized in the same manner as above to prepare a composite powder. The resulting powder was used to evaluate dispersibility in a 1.0% aqueous sodium chloride solution in the same manner as in the above-mentioned <Test Example I>. The results are summarized in Table 6 below, together with the drying temperature during powder preparation.
[0087] [Table 6]
[0088] As shown in Table 6 above, the lower the drying temperature (product temperature), the greater the viscosity, and the better the dispersion of the composite powder in the sodium chloride aqueous solution.
[0089] <Test Example V> As the solution of bacterial cellulose cultured with the first polymeric substance complexed, the same NFBC-HPC solution with a concentration of 1% by weight as described above was used, and as the second polymeric substance solution, an aqueous solution containing 1% by weight xanthan gum and 8% by weight dextrin as described above was prepared. 100 g of the NFBC-HPC solution and 100 g of the second polymeric substance solution were mixed, and a bacterial cellulose complex powder (NFBC-HPC powder) was prepared in the same manner as in the above-mentioned <Test Example I>. The bacterial cellulose composite powder thus obtained is designated as sample (V-1). The blending ratio of the cultured bacterial cellulose and xanthan gum in sample (V-1) is about 5:5.
[0090] 0.1 g of NFBC-HPC powder (sample (V-1)) was added to 100 mL of distilled water and dispersed by manual stirring in the same manner as in Test Example 1. The viscosity (20°C, 6 rpm) after 10 minutes of standing was 300 mPa s. The viscosity (20°C, 6 rpm) was measured in the same manner, except that the distilled water was replaced with a 1.0 wt% aqueous sodium chloride solution, and was 280 mPa s. The viscosity ratio was calculated to be 98.3%.
[0091] When bacterial cellulose cultured in a complex with a predetermined first polymeric substance is further complexed with a predetermined second polymeric substance (xanthan gum), a bulking agent (dextrin) may be contained as long as the blending ratio of the cultured bacterial cellulose to the second polymeric substance is within the range of 8:2 to 2:8. The obtained bacterial cellulose complex powder is well dispersed by manual stirring not only in distilled water but also in a 1.0 wt% sodium chloride aqueous solution. In this case, the viscosity value in the sodium chloride aqueous solution is 30% or more of the viscosity in distilled water, and it was confirmed that sufficient viscosity was developed.
[0092] In addition, a composite powder was prepared in the same manner as sample (V-1) except that xanthan gum was replaced with sodium alginate and dextrin was replaced with lactose (sample (V-2)). The blend ratio of cultured bacterial cellulose and sodium alginate in sample (V-2) was approximately 1:1. Using the powder of sample (V-2), the viscosity (20°C, 6 rpm) was measured in distilled water and in a 1% by weight aqueous sodium chloride solution in the same manner.
[0093] As a result, the viscosity was 150 mPa s in distilled water and 50 mPa s in sodium chloride aqueous solution, and the viscosity ratio was calculated to be 33.3%. As with sample (V-1), sample (V-2) also shows that the bacterial cellulose cultured in a complex with a specified first polymeric substance is further complexed with a specified second polymeric substance, and thus exhibits sufficient viscosity.
[0094] Furthermore, a powder of a complex was prepared in the same manner as sample (V-1) except that NFBC-HPC was changed to NFBC-CMC (sample (V-3)). The blending ratio of the cultured bacterial cellulose and xanthan gum in this sample (V-3) was about 5:5. Furthermore, using each powder of SunArtist (registered trademark) PN and SunArtist (registered trademark) PG as the fermented cellulose powder, the viscosity (20°C, 6 rpm) in a 1 wt% sodium chloride aqueous solution was measured in the same manner. Since all powders were not bacterial cellulose cultured in a complex with a predetermined first polymeric substance and further complexed with a predetermined second polymeric substance, the viscosity was 0 mPa·s.
[0095] The photographs in Figure 1 show how each powder was added to distilled water at a concentration of 0.1% by weight and dispersed by hand stirring. Figure 1(a) shows the NFBC-HPC powder, Figure 1(b) shows the NFBC-CMC powder, Figure 1(c) shows the Sun Artist PN, and Figure 1(d) shows the Sun Artist PG. In the case of distilled water, not only the NFBC-HPC powder (Figure 1(a)), but also the NFBC-CMC powder (Figure 1(b)), Sun Artist PN (Figure 1(c)), and Sun Artist PG (Figure 1(d)) were all well dispersed by hand stirring.
[0096] The photograph in Figure 2 shows the state in which the same powder was added at a concentration of 0.1% by weight to a 1% by weight aqueous sodium chloride solution and dispersed by hand stirring. Figure 2(a) is a photograph of NFBC-HPC powder, Figure 2(b) is a photograph of NFBC-CMC powder, Figure 2(c) is a photograph of Sun Artist PN, and Figure 2(d) is a photograph of Sun Artist PG. It is clearly shown that only the bacterial cellulose composite powder of the present invention (NFBC-HPC powder) can be dispersed well in the 1% by weight aqueous sodium chloride solution.
Claims
1. Bacterial cellulose is cultured in the presence of a first polymeric substance comprising at least one of hydroxypropyl cellulose and hydroxyethyl cellulose; After the cultivation, a second polymeric substance consisting of at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, xanthan gum, sodium alginate, and polyglycolic acid is added, and the mixture is dried to obtain a bacterial cellulose composite powder, The bacterial cellulose composite powder has a weight ratio of the cultured bacterial cellulose to the second polymeric substance (cultured bacterial cellulose:second polymeric substance) within a range of 8:2 to 2:
8.
2. 2. The bacterial cellulose composite powder according to claim 1, wherein the ratio of the first polymeric substance in the cultured bacterial cellulose is within a range of 5 to 50% by weight.
3. The bacterial cellulose composite powder according to claim 1 or 2, characterized in that the viscosity η(s) (mPa·s) at 20°C after adding the powder to a 1.0 wt% aqueous sodium chloride solution at a concentration of 0.1 wt%, manually stirring, and allowing to stand for 10 minutes satisfies the relationship represented by the following formula: η(s)≧50 η(s) ≧ 0.3 × η(w) (Here, η(w) is the viscosity at 20°C after adding bacterial cellulose composite powder to distilled water at a concentration of 0.1% by weight, stirring by hand, and leaving it to stand for 10 minutes.)
Citation Information
Patent Citations
Power line conveying and controlling system
JP1982052332A
Composition for stabilizing dispersion of food product
JP1997121787A
Disperse stabilization composition for heat sterilization-treated food and its use
JP1999178516A
Method for screening microorganism producing cellulose by means of water-soluble cellulose ether, bacteria cellulose and method of producing bacteria cellulose
JP2002262898A
Dry solid article of cellulose nanofiber and manufacturing method thereof
JP2017008176A